MAIN PROBLEMS WHICH HAVE IMPOSED THE TRANSPARENCY OF PUBLIC FINANCING OF POLITICAL PARTIES OF UKRAINE IN 2016 - FIRST HALF OF 2019 - Зерницький, Р. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The major issues faced by experts during the monitoring and analysis of Ukrainian political parties' public financial statements during 2016 – the first half of 2019, and which prevented the transparency of funding for a large number of parties are considered. These problems include: gaps in legislation (which allowed party members not to declare sponsorship and the operation cost of centers that were not registered as legal entities), lack of reports from the parties from the National Agency for the Prevention of Corruption (due to which part of the reports remained unpublished), inefficiency of the system of penalties for violation of financial reporting requirements (which can cause even more violations of requirements for financial statements in the future), ineffectiveness of the NAPC (due to which a large number of potential violations identified by experts remained unattended by the authorities), ability for parties to use public organizations to campaign and conceal contributions (since NGOs are not required to submit public reports on their activities), the use of third parties' personal data by party officials to conceal information about genuine party donors (which is not only criminally punishable, but also completely contradicts the idea of the existence of public financial reports of political parties).It is stated that the problem of the optionality of declaring sponsorship contributions has already been solved through an approved methodology for evaluating them, and the inefficiency of the NAPC can be eliminated by the recently signed President's Law. However, it will be possible to see the results of implementation of this law only after it becomes valid and monitors the activities of the renewed NAPC. It was concluded that resolving these problems requires a quality restart of the NAPC and changes to the legislation.